Orthodontic management of angle Class III malocclusion with severe anterior crowding - Retyoningrum, Gita; Paskalin, Zenith; Sayuti, Elih; Laviana, Avi; Evangelina, Ida Ayu; Mardiati, Endah (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Dental malocclusion Class III is a challenging condition characterized by a Class III molar relationship, and it has a specific anterior condition according to Dewey classification. In some cases, Class III dental malocclusion with skeletal Class I may present with a convex rather than a concave profile. Several methods are available to correct a convex profile, including extraction, full arch distalization using TADs, intermaxillary elastic Class II, anterior segment retraction, and others. Combining more than one of these methods can be effective in correcting a convex profile. An 18 year-old woman presented to RSGM Universitas Padjadjaran with a diagnosis of Angle Class III dental malocclusion, skeletal Class I with a convex profile, normal maxillary incisor inclination, asymmetric profile, severe anterior crowding in both arches, minimal overjet, anterior crossbite, upper midline shift, clockwise rotation and high-angle mandible, and lingual inclination of the mandibular incisors. The patient was treated with a Roth prescription fixed orthodontic appliance. Maxillary and mandibular first premolars were extracted to create space, and lacebacks were applied to the canines to correct severe anterior crowding]. Bilateral intermaxillary Class III elastics were used to maintain the facial profile and prevent it from becoming concave. Treatment was completed in 18 months, achieving a Class I molar relationship, midline correction, optimal overbite and overjet, and preservation of the facial profile. This case report presents the orthodontic management of Angle Class III malocclusion with skeletal Class I and severe anterior crowding, successfully treated with first premolar extractions while maintaining a convex profile.